(untitled) (Bangladesh Journal of Infectious Diseases, 2015)
Dengue represents common endemic infection in tropical areas. Occurrence of bacterial and fungal superinfection or coinfection in patients with dengue is rare. In case of persistent fever in patients with dengue, co-infection with bacteria and fungi should be kept in mind and patients should be investigated accordingly. We report an unique case of an infant with severe dengue fever presenting as meningoencephalitis with co-infection with Hemophilus Influenza and Candida tropicalis. Bangladesh Journal of Infectious Diseases 2014;1(2):38-40